Comparative analysis of PV technologies across diverse solar regions using sustainability metrics - Rasha Elazab; Mohamed Daowd (Energy Informatics)
Abstract Achieving Sustainable Development Goal 7 (SDG7: Affordable and Clean Energy) and Sustainable Development Goal 13 (SDG13: Climate Action) requires advancing renewable energy systems with enhanced sustainability and resilience. Traditional Photovoltaic (PV) planning often focuses on average energy output, overlooking critical metrics such as consistency, variability, and long-term performance. This study analyzes three consecutive years (2017–2019) to assess the impact of climate variability on the energy trends of three PV technologies, fixed PV, Concentrated PV (CPV), and Dual Axis Tracking PV (DATPV), across six global cities. Sustainability scores were calculated using a GIS-based metric that captures energy consistency, intermonthly variability, and climatic adaptability, providing a technical evaluation of long-term system stability under varying weather conditions. The results reveal Cairo and Riyadh as top performers, achieving sustainability scores of 0.87 and 0.70, respectively, for fixed PV in 2019. In Madrid, DATPV systems excelled with sustainability scores reaching 0.39 in 2019, leveraging abundant solar resources. Meanwhile, Beijing’s fixed PV systems demonstrated exceptional stability, maintaining scores of 0.58 across all years, reflecting the region’s consistent solar conditions. By integrating sustainability metrics, this study offers a comprehensive framework for evaluating PV systems under changing climatic conditions, advancing SDG7 by ensuring reliable energy access and SDG13 by promoting resilient, climate-adaptive renewable energy solutions.